Chlorella vulgaris -mikrolevän hyödyntäminen kalojen kiertovesikasvatuksen ravinne- ja hiilidioksidipäästöjen talteenotossa - Söderena, Olivia (2024)
Continuously growing population on Earth and accelerating climate change have together led to a situation where there is a need for new sustainable methods for food production. One possible sustainable alternative is a recirculating aquaculture system (RAS). The sustainability of RAS can be further improved by utilizing its wastewater in the cultivation of microalgae which would purify the wastewater at the same time. This study investigated the ability of Chlorella vulgaris microalgae to collect nutrients and carbon dioxide from RAS wastewater. The study compared growth and biochemical properties, such as carotenoid content, of C. vulgaris in four different treatments. The treatments consisted of two different factors, the culture medium and the CO2 concentration used in the aeration of the cultures. Culture medium was either RAS wastewater or MWC medium (modified Wright’s cryptophyte medium) as a control. Algae cultures were aerated either with the exhaust air from the RAS trickling filter with higher CO2 concentration (average during cultivation 809±132 ppm), or with room air as a control (average during cultivation 375±8 ppm). Microalgae grown in RAS wastewater had higher dry weight, growth rate and chlorophyll a content compared to algae grown in MWC medium. In addition, the removal efficiencies of nutrients, nitrate nitrogen (NO3-N) and orthophosphate (PO4-P), were higher in algae grown in RAS wastewater than in MWC medium. The proportions of carbon and lipids in the dry weight were higher in algae grown in MWC medium, while the proportion of nitrogen was higher in algae grown in RAS wastewater. Significant differences were observed between fatty acid groups between treatments, while no significant differences were observed in carotenoid concentrations. The CO2 concentration of aeration did not significantly increase the growth or other properties of the algae, but on the other hand, no negative effects were found either. Based on this and previous studies, C. vulgaris microalgae can be used in the purification of RAS wastewater, and there are possibilities for further use of the grown algae. However, industrial utilization of C. vulgaris in RAS wastewater treatment still requires more research to maximize the productivity of biochemical properties.